Key aspects of the past 30 years of protein design. (1st August 2022) - Magi Meconi, Giulia; Sasselli, Ivan R; Bianco, Valentino; Onuchic, Jose N; Coluzza, Ivan
Abstract: Proteins are the workhorse of life. They are the building infrastructure of living systems; they are the most efficient molecular machines known, and their enzymatic activity is still unmatched in versatility by any artificial system. Perhaps proteins' most remarkable feature is their modularity. The large amount of information required to specify each protein's function is analogically encoded with an alphabet of just ∼20 letters. The protein folding problem is how to encode all such information in a sequence of 20 letters. In this review, we go through the last 30 years of research to summarize the state of the art and highlight some applications related to fundamental problems of protein evolution.